Molecular surveillance of dengue virus in field-collected Aedes mosquitoes from Bhopal, central India: evidence of circulation of a new lineage of serotype 2 - Sarma, Devojit Kumar; Rathod, Lokendra; Mishra, Sweta; Das, Deepanker; Agarwal, Ankita; Sharma, Gaurav; Singh, Tanim Arpit; Kumawat, Manoj; Singh, Samradhi; Verma, Vinod; Kumar, Manoj; Shubham, Swasti; et al. (Frontiers in Microbiology, 2023)
Introduction Dengue fever is hyperendemic in several Southeast and South Asian countries, including India, with all four serotypes (DENV 1–4) circulating at different periods and in different locations. Sustainable and improved virological and entomological surveillance is the only tool to prevent dengue and other vector-borne diseases. Objectives The present study has been carried out to detect and characterize the circulating dengue virus (DENV) in field-collected Aedes mosquitoes in Bhopal, Central India. Methods Aedes mosquitoes were collected from 29 localities within Bhopal city during October 2020 to September 2022. DENV infection was assessed in the individual head and thorax regions of Aedes mosquitoes using reverse transcriptase PCR. Positive samples were sequenced, and the circulating serotypes and genotypes were determined using phylogenetic analysis. Results DENV RNA was detected in 7 Aedes aegypti and 1 Aedes albopictus, with infection rates of 0.59 and 0.14%, respectively. Phylogenetic analysis revealed all the isolates belonged to DENV serotype 2 and distinctly clustered with the non-Indian lineage (cosmopolitan genotype 4a), which was not recorded from the study area earlier. The time to most common recent ancestor (TMRCA) of these sequences was 7.4 years old, with the highest posterior density (HPD) of 3.5–12.2 years, indicating that this new lineage emerged during the year 2014. This is the first report on the DENV incrimination in both Ae. aegypti and Ae. albopictus mosquitoes collected from Bhopal, Central India. Conclusion The observed emergence of the non-Indian lineage of DENV-2 in Bhopal, which again is a first report from the area, coincides with the gradual increase in DENV cases in Bhopal since 2014. This study emphasizes the importance of DENV surveillance and risk assessment in this strategically important part of the country to decipher its outbreak and severe disease-causing potential.